Mental health and associated factors among people with mobility disability disabilities in central provinces of VietNam - Nguyen, Thi Mai Hien (Đại học Quốc gia Hà Nội, 2020)
Vietnam has made strong commitments to support people with disability ( PWD ) by inuing the Law for PWD in 2010, and ratifying the United National Convention on the Rights of Persons with Disabilities in 2014. Mobility impairment accounts for around 50 percent of total number of PWD. The health and well - being outcomes for PWD cannot be achieved without mental health care support. Thus , this research aimed to identify the mental health problems and associated factors of the selected people with mobility disabilities ( PWMDs ) in the three provinces. The research adopted a descriptive cross - sectional study design . 334 PWMDs in Thua Thien Hue , Quang Nam and Binh Dinh were interviewed . Survey tools included WHO 12 - item Disability Assessment Schedule to measure functional level of activities and participation ; and the Depression , Anxiety and Stress Scales developed by The University of New South Wales , and approved by Ministry of Health of Vietnam to be used for screening and measuring level of depression , anxiety and stress . The research showed that there was a high proportion of PWMDs with symptoms of depression ( 38.4 % ) , anxiety ( 43.1 % ) and stress ( 23.4 % ) . Of PWMDs displaying severe and very severe symptoms , 12.0 % were found to experience depression , 9.9 % for anxiety , and 5.4 % for stress. PWMDs who are not working. who are poor or near poor, who need help from the others , who have functioning difficulties, are more likely to have mental health problems than those who are working, non - poor, can live independently, have less functioning difficulties. With high rates of PWMDs having symptoms of common mental disorders, specific mental health intervention programs for PWMD need to be developed and implemented with different levels of care to support those with different levels of severity. The factors associated with mental health problems will also need to be taken into consideration during development and implementation of the intervention